Critical Financial Challenges for Biobanking: Report of a National Cancer Institute Study - Rao, Abhi (Biopreserv Biobank, 2019)
Background: Researchers and other key stakeholders in biobanking often do not have a thorough understanding of the true costs and challenges associated with initiating, running, and maintaining a biobank. The National Cancer Institute's Biorepositories and Biospecimen Research Branch (BBRB) commissioned the Biobanking Financial Sustainability survey to better understand the challenges that biobanks face in supporting ongoing operations. A series of interviews with biobanking managers and an international focus group session informed the content of the survey. Methods: The design of the survey included five main sections, each containing questions related to primary topics as follows: general demographics, operations, funding sources, costs, and financial challenges. While the survey focused on financial issues and challenges, it also explored staffing and strategic planning as these issues relate to the sustainability of operations and financial support. U.S. and international biobanks were included in the survey. Results: Biobanks in general are dependent on public funding and most biobanks do not have formal plans for the long-term stewardship of their collections. Respondents are working at a critical level of personnel and are not in a position to further reduce staffing. Smaller biobanks in particular need assistance in defining reasonable cost recovery user fees for biospecimens and related services. Conclusions: The survey results highlight several issues that are important for long-term biobank sustainability. It is critical to prepare for such issues as effective biobanking practices have increasingly been recognized as a key component for the advancement of precision medicine.